Possibilidades da emancipação humana em práticas educativas da educação física escola - Vieira, Marcos Araújo (2002)
This research is about the possibilities of fomenting the human emancipation in classes of school physical education, in a school of the public net of teaching, of Santa Maria's city, RS. We looked for through the analysis of the Pedagogic Political Project and of the School Regiment and information on its associate economical conditions, as well as through interviews semistructured with teachers and students to investigate the possibility to foment the human emancipation in educational practices of the physical education. We concluded that there are fomentation possibilities to the human emancipation in educational practices of the physical education. We proposed for that some actions that were shown possible in the interpretation of the information. One of the actions proposals went the amplification of to the school community's of the actions participation in the implementation of the Pedagogic Political Project and of the School Regiment. Other, it went to organization of continuous formation to the segments of the school. We still ended, if necessary an engagement on the part of the teachers of physical education in the work of resignification of its educational practices guided for formation and the fomentation of the human emancipation.